2019
DOI: 10.1016/j.ssmph.2018.100331
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in end-of-life care in the United States: Evidence from the Health and Retirement Study (HRS)

Abstract: Population ageing poses considerable challenges to the provision of quality end-of-life care. The population of the United States is increasingly diverse, making it imperative to design culturally sensitive end-of-life care interventions. We examined participants of the Health and Retirement Study, who died between 2002 and 2014, to examine racial and ethnic differences in end-of-life care utilization and end-of-life planning in the United States. Our study reveals significant disparities in end-of-life care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 34 publications
2
71
2
Order By: Relevance
“… 10 Although findings from the USA have suggested that these strategies have had limited impact in the uptake of palliative care services among migrant communities. 11 Other recent initiatives have recommended the need to gather more on the experiences and needs of population groups that access less palliative care. 9…”
Section: Introductionmentioning
confidence: 99%
“… 10 Although findings from the USA have suggested that these strategies have had limited impact in the uptake of palliative care services among migrant communities. 11 Other recent initiatives have recommended the need to gather more on the experiences and needs of population groups that access less palliative care. 9…”
Section: Introductionmentioning
confidence: 99%
“…( 24 ) Some of these findings may reflect cultural differences in preferences for end of life as well as potential socioeconomic or cultural barriers such as the cost of hospice and access to timely advanced care planning. ( 40,41 ) Although it is reassuring that the rates of hospice adoption are increasing in Black patients, the rates still lag behind those of White patients, and further attention is necessary to ensure that rates equalize.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that Black and Hispanic workers were not able to take time off from work to take care of their family (26% and 23%, respectively; Horowitz et al, 2017). In addition, racial and ethnic minority individuals are less likely to be involved in end-of-life planning and more likely to die in hospitals as opposed to at home (Orlovic et al, 2019). Furthermore, ethnic minority individuals with low incomes reported using hospice care services less (Hughes & Vernon, 2019), which might result in additional physical, psychological, and financial burdens to the caregivers (Born et al, 2004).…”
Section: Discussionmentioning
confidence: 99%